Discovery of a notable DDT-degrading bacterium originating from insecticide-contaminated soil in Vietnam and representing a novel species - Vu, Phuong Ha; Tran, Linh Phuong; Vu, Tung Son; Tran, Trang Quynh Thi; Nguyen, Yen Thi; Hoang, Anh Quynh; Nguyen, Thao Kim Nu; Nguyen, Minh Hong; Kim, Song-Gun; Tran, Huyen Thanh Thi; Pham, Hai The (Frontiers in Microbiology, 2026)
Dichlorodiphenyltrichloroethane (DDT), one of the earliest and most extensively used synthetic insecticides, has become a persistent organic pollutant of global concern due to its high recalcitrance and hydrophobicity (resulting in its poor water solubility and long-term accumulation in soils and sediments). In this study, 207 bacterial strains were isolated from DDT-contaminated soils and screened for their ability to grow on DDT-containing media. Among them, 10 strains exhibited remarkable tolerance and growth, with strain T006 showing the highest potential for DDT degradation. Further experiments demonstrated that T006 exhibited strong and progressive DDT-degrading activity, removing over 70% of DDT within 8 weeks of culture. Comprehensive phenotypic, chemotaxonomic, and genome-based analyses — including 16S rRNA gene and rpoD gene phylogeny, average nucleotide identity (ANI), and digital DNA–DNA hybridization (dDDH) — confirmed that strain T006 represents a novel species, designated as Pseudomonas vietnamensis. The discovery of Pseudomonas vietnamensis T006 expands the known diversity of DDT-degrading bacteria and provides a promising microbial resource for the development of effective bioremediation strategies targeting organochlorine pesticide–contaminated environments.